Identification of common and novel major crab allergens in scylla tranquebarica and the allergen stability in untreated and vinegar-treated crab - Hasan Ali Jasim (Tanjung Malim, 2021)
Identification of common and novel major crab allergens in scylla tranquebarica and the allergen stability in untreated and vinegar-treated crab by Hasan Ali Jasim